Biological control of fungal pathogens of tomato (Lycopersicon esculentum) by chitinolytic bacterial strains. (10th December 2021) - Malik, Muhammad Saqib; Haider, Shabeer; Rehman, Abdul; Rehman, Shafiq Ur; Jamil, Muhammad; Naz, Iffat; Anees, Muhammad
Abstract: The need to increase food production and to reduce the pollution caused by synthetic chemicals has led to a search for biocontrol agents against plant pathogens. In the present study, a total of 37 chitinolytic bacteria were isolated from the rhizospheric soil of tomatoes using a chitin agar medium. In vitro bacterial isolates, that is, TD9, TD11, TD15, and TD24 showed strong antagonistic and enzymatic activities against Rhizoctonia (8%–55%), Fusarium (31%–48%), Colletotrichum (24%–49%), and Aspergillus on a dual culture plate and enzyme assay. Furthermore, these putative antagonistic bacterial isolates were identified as Pantoea agglomerans (TD9), Bacillus subtilis (TD11), Bacillus cereus (TD15 and TD24) using 16S rRNA sequence analysis. Additionally, in culture filtrate in vivo assay, the isolates TD11 and TD15 inhibited the growth of Rhizoctonia solani about 40% and Fusarium oxysporum about 80%. However, in the pot trials, these two bacterial isolates (TD11 and TD15) considerably suppressed the disease rate in tomatoes caused by Fusarium and Rhizoctonia fungal species. Moreover, it was concluded that B. subtilis (TD11) was found to be the most promising putative biocontrol agent, inhibiting the fungal diseases of tomatoes by 50% and showing versatile antagonistic potential.